Splenic Parenchymal Complications in Pancreatitis - Patil, Pradeep V; Khalil, Ahmed; Thaha, Mohamed A (JOP. Journal of the Pancreas, 2011)
Context The close proximity of splenic hilum to the tail of pancreas makes it vulnerable to complications in both acute and chronic pancreatitis. In this article, we examine the clinical course of these potentially fatal complications. Case reports Citing three clinical cases, we present the spectrum of splenic complications in pancreatitis and explore the anatomical causal relationships and pathological basis of such complications. A literature review was carried out to inform on the incidence, morbidity and mortality rates, and clinical course especially diagnostic and management options for these patients. The spectrum of splenic complications in pancreatitis is wide ranging from pseudo cysts to haematomas, haemorrhages, infarctions and life threatening splenic rupture. Although a contrast enhanced helical CT scan is the investigation of choice a high index of clinical suspicion is essential in their early identification. Splenic complications in pancreatitis incur a high morbidity (79%) and a significant mortality (8%). Conclusions Splenic parenchymal complications in pancreatitis are an increasingly recognised entity and should be suspected in patients with inflammation and or necrosis involving the tail of pancreas. Conservative management is feasible with close radiological monitoring for most patients in a tertiary referral centre with appropriate expertise and surgery may be reserved for haemodynamically unstable patients. Image: Splenic sub-capsular haematoma.